CHILDFREE DAN MENGATUR KELAHIRAN MENURUT HUKUM ISLAM - Siregar, Rika Diana; Hasanah, Uswatun (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2025)
Childfree is an agreement made by a husband and wife not to have children during their marriage. There are manyreasons why someone and their partner have a view like this. The reasons are: (1) Economic Factors, (2) Mental orPsychological Factors, (3) Personal Factors and Experience, (4) Environmental Factors, (5) Medical Factors, and(6) Educational Factors. This research examines childfree from an Islamic perspective which aims to discuss thephenomenon of childfree which is being stirred up and reaping debate in society and is motivated by cases that arecurrently being discussed. This study uses a qualitative approach by using a literature review in collecting data. Thesources used as references in this research are the Al-Qur'an, scientific journals, Hadith, and other sources. In Fiqh,childfree is a decision that is prohibited in Islam because the application of childfree is based on reasons that seemtoo mundane such as the economy, education, environment, and others. Whereas in Islam it has been explained thatchildren have many advantages and blessings in this world and the afterlife. Even though no verse directly prohibitschildfree, the choice for childfree-ness can be said to be a choice that cannot be justified or blamed because it is anindividual right or with the family which cannot be intervened by other people's views.